Digital Marketing and Traveloka App User Interest - Pradini, Gagih; Ernowo, Atha Fadhil; Awaloedin, Dipa Teruna (International Journal of Education, Information Technology, and Others, 2024)
The rapid development of information and communication technology has had a significant impact on various sectors, including the tourism industry. Digital marketing is becoming one of the important tools for the tourism industry to reach consumers and increase sales. This paper examines the use of digital marketing by Traveloka, a lifestyle superapp in Southeast Asia, in reaching consumers and improving services. SWOT analysis is used to identify strengths, weaknesses, opportunities, and threats faced by Traveloka in the context of digital marketing. The analysis results show that Traveloka has several strengths, including broad reach, precise targeting, two-way interaction, and engaging content. However, weaknesses such as fierce competition, ad saturation, reliance on technology, and fraud risk were also identified. Emerging opportunities include internet user growth, new technological developments, personalization, and influencer marketing. Meanwhile, threats include algorithm changes, stricter privacy policies, consumer mistrust, and the emergence of new platforms. Based on these findings, Traveloka can develop effective digital marketing strategies with a focus on long-term relationships with customers and multi-channel integration. Suggestions for improvement include periodic market research, development of an integrated digital marketing strategy, creation of engaging content, and utilization of influencer marketing. With these steps, Traveloka is expected to continue to be the leading travel platform in Southeast Asia.